Judging commercial surrogacy and public policy: an analysis of Whittington Hospital NHS Trust v XX (UK Supreme Court) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Our contribution offers an analysis of the UK Supreme Court judgment in the case of Whittington Hospital NHS Trust v. XX, regarding the possibility of considering the costs for commercial surrogacy arrangements in California as a recoverable head of damage. The commentary analyses the divergent conceptions of public policy and legal policy illustrated in the majority and dissenting opinions. In conclusion, an assessment is given of the scope and extent of the judgment, in the light of past cases and with a view to the possible influence of the decision on future claims for damages.
Keywords: Surrogacy; UK Supreme Court; legal policy; public policy; ethics